Analisis Problematika Kurikulum Merdeka pada Mata Pelajaran Kimia di Sekolah Menengah Atas - Evi Tri Uthami; Rifa Rafifah Salsabila; Rizka Nazwatul Ilmi; Tisdiawati Intan Pandini (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research aims to analyze the problems of implementing the independent curriculum at high school level, especially in chemistry subjects. The research method used in this research is using a qualitative method by collecting data via Google Form in the form of an open questionnaire and literature study methods. There were 39 respondents from class X, XI and XII students. The results of the research show that there are several problems in implementing the independent curriculum, including some students still experiencing difficulties in understanding chemistry material, difficulties because literacy requires searching for material before learning, and school facilities that do not support the implementation of the independent curriculum. But on the other hand, some students say otherwise. In conclusion, there is a need for a comprehensive evaluation of the implementation of the Independent Curriculum in chemistry subjects in high school with a focus on student understanding, the role of teachers, resources and school support, apart from the statements of students who already think positively about the implementation of the independent curriculum in chemistry subjects.